Epidemiology and clinical characteristics of human rhinovirus in hospitalized children and adolescents with acute respiratory infections: a longitudinal study in Shenzhen, China (2019–2024) - Jiao Liu; Wei Wang; Ke Cao; Zhenmin Ren; Xiaoying Fu; Yunsheng Chen; WenJian Wang; Yuejie Zheng; Yanmin Bao; Xiaojuan Luo; Jiehua Chen (Virology Journal)
Abstract Background Human rhinovirus (HRV) is a significant pathogen responsible for acute respiratory infections (ARIs) in children and is closely associated with pediatric wheezing. However, its clinical importance remains a subject of debate. This study aims to investigate the epidemiology, clinical characteristics of HRV, and to explore the impact of the Coronavirus Disease 2019 (COVID-19) pandemic and non-pharmaceutical interventions (NPIs) on HRV dynamics. Methods A retrospective analysis was conducted on HRV-positive cases among children and adolescents hospitalized for ARIs at a tertiary medical center in Shenzhen, China, from September 2019 to December 2024. Multiplex PCR was employed to detect 12 common respiratory pathogens, and molecular typing of HRV was performed on selected bronchoalveolar lavage fluid (BALF) samples. Demographic data, epidemiological patterns, co-infection profiles, clinical characteristics were analyzed. Data were stratified into three periods based on COVID-19 pandemic and NPIs implementation: pre-pandemic (September–December 2019), pandemic (2020–2022, with NPIs in effect), and post-pandemic (2023–2024, after NPIs cessation). Results Among 74,330 children and adolescents hospitalized for ARIs, HRV was detected in 18,681 cases (25.13%), exhibiting year-round prevalence with seasonal peaks in spring and autumn. HRV-A (62.84%) was the predominant genotype, followed by HRV-C (28.38%). Co-infections occurred in 32.00% of HRV cases and were associated with higher rates of pneumonia and severe pneumonia (P < 0.001). Conversely, HRV mono-infections were significantly correlated with hospitalizations for acute wheezing illnesses and more severe clinical outcomes (all P < 0.001). During the stringent NPIs period (early 2020), HRV detection rates declined markedly but rebounded rapidly following the relaxation of measures. The overall HRV positivity rate post-pandemic (25.53%) was significantly higher than that during the pandemic (23.50%, P < 0.001). The median age of HRV-infected children and adolescents increased significantly from 1.83 years pre-pandemic to 2.25 years during the pandemic to 3.33 years post-pandemic (P < 0.0001). However, clinical severity indicators for HRV mono-infections remained largely unchanged between the pandemic and post-pandemic periods. Conclusion HRV is a major pathogen in pediatric ARIs, with HRV mono-infections strongly associated with hospitalizations for acute wheezing illnesses and severe clinical outcomes. Unlike other respiratory viruses, HRV demonstrated relative resilience to NPIs and a notable post-pandemic shift in the age distribution of infections toward older children. These findings underscore HRV’s ongoing public health significance and the necessity for continued surveillance.